The seven S.E.C.R.E.T.S. of the money masters - Shemin Robert , 1963-; Hirsch, Peter , 1965- (John Wiley & Sons, 2010)
"Two bestselling authors present an easily accessible approach to managing finances Your financial advisor is not someone you should have doubts about. But, in today?s economic environment, can they be trusted to tell you the truth? The fact is information is power. And, the truth is there?s lots of financial advice available. Unfortunately, it?s often either too confusing or biased. The Seven S.E.C.R.E.T.S. of Money Masters cuts through the clutter, clearly presenting the seven most important questions to ask your financial planner before trusting him or her with your hard-earned money. Addresses those things most financial advisors fail to mention, and shines a light on the much broader issues of attaining wealth and getting your retirement plans back on track. S.E.C.R.E.T.S. website offers additional resources and access to exclusive debt reduction software. Other titles by Shemin: 40 Days to Success in Real Estate Investing and Secrets of Buying and Selling Real Estate...Without Using Your Own Money!, both by Wiley. The Seven S.E.C.R.E.T.S. of Money Masters goes where most personal finance books -and financial advisors - fear to tread, revealing the S.E.C.R.E.T.S. of Safety, Expense, Cash Flow, Rate of Return, Economy, Tax Efficiency and (common) Sense"-- Provided by publisher